Assessment of the Prevalence of Hepatitis A in Children in Yasuj - AK Ghadimi-Moghaddam (Armaghane Danesh Bimonthly Journal, 2021)
Background & aim: Hepatitis A is one of the most common viral infections in children that affects the liver and may be with or without symptoms. The disease is transmitted through oral-fecal excretion and its prevalence is clearly related to the level of health of the target community and is therefore one of the health problems of the world and developing countries. Hepatitis A is present in all parts of the world, but its prevalence varies in different parts of the world. Therefore, the aim of the present study was to determine and evaluate the prevalence of hepatitis A in children in Yasuj.